Socioeconomic status and stress in Mexican–American women: a multi-method perspective - Gallo, Linda C. (2012)
Stress is a hypothesized pathway in socioeconomic status (SES)-physical health associations, but the available empirical data are inconsistent. In part, this may reflect discrepancies in the approach to measuring stress across studies, and differences in the nature of SES-stress associations across demographic groups. We examined associations of SES (education, income) with general and domain-specific chronic stressors, stressful life events, perceived stress, and stressful daily experiences in 318 Mexican–American women (40–65 years old). Women with higher SES reported lower perceived stress and fewer low-control experiences in everyday life (ps < .05), but greater chronic stress (education only, p < .05). Domain-specific analyses showed negative associations of income with chronic housing and financial stress (ps < .05), but positive associations of SES with chronic work and care-giving stress (all ps < .05 except for income and caregiving stress, p < .10). Sensitivity analyses showed that most SES-stress associations were consistent across acculturation levels. Future research should adopt a multi-dimensional assessment approach to better understand links among SES, stress, and physical health, and should consider the sociodemographic context in conceptualizing the role of stress in SES-related health inequalities.